Ameliorative Effect Of Volvariella Volvacea Aqueous Extract ( Bulliard Ex Fries) Singer On Gentamicin Induced Renal Damage - SHWETHA. V. KALAVA; SUDHA .G.MENON (International Journal of Pharma and Bio Sciences, 2012)
Mushrooms are used widely in Asian cuisines. Volvariella volvacea, commonly known as the paddy straw mushroom is an edible fungi. Mushrooms are found to be rich in phytochemicals that function as potent antioxidants. Aminoglycosides like Gentamicin, used to treat infections are reported to cause renal damage. The present study was undertaken to evaluate the capacity of the aqueous extract of Volvariella volvacea on Gentamicin induced renal damage in rats. The extract at 500 and 1000mg/kg body weight was observed to normalize the urine volume, serum and urine levels of creatinine, urea and uric acid. The mushroom extract was observed to improve the depressed antioxidant status and reduce the lipid peroxidation levels. The present study thus reveals the capacity of the extract to reverse the alterations imposed by Gentamicin.